БИОЛОГИЯ ФАНИНИ ЎРГАНИШ ЖАРАЁНИДА ТАЛАБАЛАРДА ТАЯНЧ ВА БИОЛОГИК КОМПЕТЕНЦИЯЛАРНИ ТАРКИБ ТОПТИРИШ - Утенова, Г.У. (SCIENCE and SOCIETY, 2018)
The article presents the new forms of the development of competence in the specialty in training future pedagogical staff. The author of the article emphasizes that together with upbringing and development of skills in subjects, it‘s necessary to form the competence in children during the lessons. With the purpose of performing it there were held experimental research works in academic subjects at the general educational schools, colleges and academic lyceums.
Keywords: intellectual; competence; science; expert; technology; methods; experimentalist; communicative